2016
DOI: 10.14311/gi.15.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Object Based and Pixel Based Classification Using Rapideye Satellite Imager of ETI-OSA, Lagos, Nigeria

Abstract: Several studies have been carried out to find an appropriate method to classify the remote sensing data. Traditional classification approaches are all pixel-based, and do not utilize the spatial information within an object which is an important source of information to image classification. Thus, this study compared the pixel based and object based classification algorithms using RapidEye satellite image of Eti-Osa LGA, Lagos. In the object-oriented approach, the image was segmented to homogenous area by suit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…The classification can be performed either by pixel-or object-based approaches. It has been widely demonstrated that object-based approaches can provide more accurate results when using high-and very high-resolution data [86][87][88]. In contrast, when the object's dimension is smaller than the pixel resolution (e.g., when a single-tree canopy is to be detected in images with 10 m spatial resolution), a pixel-based approach is preferable.…”
Section: Classificationmentioning
confidence: 99%
“…The classification can be performed either by pixel-or object-based approaches. It has been widely demonstrated that object-based approaches can provide more accurate results when using high-and very high-resolution data [86][87][88]. In contrast, when the object's dimension is smaller than the pixel resolution (e.g., when a single-tree canopy is to be detected in images with 10 m spatial resolution), a pixel-based approach is preferable.…”
Section: Classificationmentioning
confidence: 99%
“…In comparison with pixelbased classification, object-based classification classifies the image based on objects instead of pixels. Although this technique has been introduced in the 1970s, its application in the remote sensing field started a decade ago (Makinde et al, 2016). Even though this technique has been generally used for high and very high-resolution imagery, it has also been successfully applied in middle-resolution imagery.…”
Section: Methodsmentioning
confidence: 99%
“…There are generally two approaches for the classification: pixel-based classification (PBC) and object-based classification (OBC). PBC analyses the spectral properties of every pixel within an area of interest, without considering contextual information, such as shape (Makinde, Salami, Olaleye, & Okewusi, 2016). This approach does not produce accurate results when analysing VHR (Toll, 1984;Xia, 2007), which is due to the high spectral variability in VHR imagery.…”
Section: Satellite Image Classification For Informal Settlement Detectionmentioning
confidence: 99%